APPLICATION OF THE CONTEXTUAL TEACHING AND LEARNING MODEL THROUGH TEACHING AT THE RIGHT LEVEL ASSISTED BY CONCRETE MEDIA TO IMPROVE MATHEMATICAL PROBLEM-SOLVING SKILLS - Gunawan, Gunawan; Nisa, Izatun; Untarti, Reni; Kusuma, Jaka Wijaya; Purwanto, Joko; Susri, Susri (Yayasan Education and Social Center, 2024)
The background of the problem in this study is the low mathematical problem-solving ability and learning outcomes of grade II students of SD Negeri 1 Banjarsari Kulon. In the mathematics learning process, where students are less able to understand the material delivered by the teacher, and in doing problems do not use the solution steps, causing low students' ability to solve problems so that learning outcomes are not optimal. The research conducted during these 3 cycles aims to improve the ability to solve mathematical problems in measurement materials. Data on problem-solving skills and activities of teachers and students using observation sheets and through written tests were both quantitatively analyzed. This success indicator with an average percentage of overall mathematical problem-solving ability reaches 75%. The results of this study show that the average percentage of problem-solving ability in cycle 1 is 43% (less) to 82% (very good) in cycle III. In the aspect of completeness, learning outcomes were shown at an average of 68% completeness in cycle I and to 84% in cycle III.